Use of internal thoracic artery as a conduit protects coronary artery in the long-term period after coronary artery bypass graft surgery - A. V. Frolov; N. I. Zagorodnikov; R. S. Tarasov; E. V. Grigoriev; S. V. Ivanov; L. S. Barbarash (Фундаментальная и клиническая медицина)
Aim. To assess whether the internal thoracic artery (ITA) is able to protect coronary artery (CA) after coronary artery bypass graft (CABG) surgery.Material and Methods. Having performed coronary angiography in the long term after CABG surgery, we evaluated 102 angiograms by visual analysis and using Gensini score and SYNTAX score. Using these parameters, we investigated the association of internal thoracic artery and saphenous vein grafts with anatomy and pathology of the coronary artery.Results. Calculation of Gensini score revealed that use of ITA grafts was associated with mild coronary atherosclerosis [4 (0; 17)] as compared with SV grafts [32 (2 ; 32)]. Relative increase of atherosclerotic burden in the coronary artery was 21.05% for the ITA grafts and 102.87% for the SV grafts. Lesion growth rate was significantly higher after using SV grafts than in case with ITA grafts (p = 0.0002)Conclusion. ITA grafts reduce progression of atherosclerosis in bypassed coronary arteries in comparison with SV grafts.